Performance of SMEs: Literature synthesis of contingency models - Humberto Ramirez; Lim, Thien Sang (LLC “Consulting Publishing Company “Business Perspectives”, 2021)
The fundamental issue of performance of SMEs has been intensively analyzed by academia mainly through performance models. Performance models are largely focused on predicting failure and have intrinsic limitations. The present literature synthesis proposes an alternative perspective from seemingly unconnected empirical studies, which share the performance of SMEs as a common criterion: contingency models. Such perspective emphasizes the positive facet of SMEs results and complements the current academic standard of prediction models. This study performed integration and conceptual classification of 99 articles cataloged as contingency models and published by reputed journals from 1999 to 2019. The evidence from the integrated empirical literature revealed an ample and diverse set of supported variables that explain a positive economic outcome in small ventures. The analysis and classification of the articles derived 7 sections, 24 categories and 131 supported variables, which are intended to help improve the scholarly and professional analysis of SME performance due to the inherent viability of the integrated articles, proving a benign economic output. This view contradicts the current paradigm of performance models, which is insufficient to predict or explain how to improve SMEs results. The integrated elements developed by this study can work as a framework for the academic research of SMEs performance, and practical guidance for SMEs’ managers. This synthesis sets an agenda for further academic research in the field of SME performance, specifically in the areas of methodology, operationalization of performance, and empirical research.